Tingkat Kesejahteraan Psikologis Mahasiswa Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya - Rahimsyah, Anandha Putri; Muhajirin, Muhammad (Universitas Mathla'ul Anwar Banten, 2025)
The study aims to measure the level of achievement of students' psychological well-being which affects all aspects of their lives, especially during the transition period. The study used a descriptive quantitative method with a sample of 275 active students of the guidance and counseling study program at the University of Muhammadiyah Tasikmalaya. The results of the study showed that students had achieved psychological well-being in the high and medium categories. This means that most students have achieved an optimal level of psychological well-being characterized by having self-acceptance, autonomy or independence, being able to establish positive relationships with others, having good mastery of the environment, having a purpose in life, and being able to develop themselves in a better direction. The factors that influence its achievement are discussed in the article and have implications for guidance and counseling services in college counseling.